Rapid Transition of a PICU Space and Staff to Adult Coronavirus Disease 2019 ICU Care. Issue 1 (January 2021) - Wasserman, Emily; Toal, Megan; Nellis, Marianne E.; Traube, Chani; Joyce, Christine; Finkelstein, Robert; Killinger, James S.; Joashi, Umesh; Harrington, John S.; Torres, Lisa K.; Greenwald, Bruce M.; Howell, Joy
Abstract : Objectives: We describe the process by which a PICU and a PICU care team were incorporated into a hospital-wide ICU care model during the coronavirus disease 2019 pandemic. Design: A descriptive, retrospective report from a single-center PICU. Setting: Twenty-three bed, quaternary PICU, within an 862-bed hospital. Patients: Critically ill adults, with coronavirus disease 2019-related disease. Interventions: ICU care provided by pediatric intensivists with training and support from medical intensivists. Measurements and Main Results: Within the context of the institution's comprehensive effort to centralize and systematize care for adults with severe coronavirus disease 2019 disease, the PICU was transitioned to an adult coronavirus disease 2019 critical care unit. Nurses and physicians underwent just-in-time training over 3 days and 2 weeks, respectively. Medical ICU physicians and nurses provided oversight for care and designated hospital-based teams were available for procedures and common adult emergencies. Over a 7-week period, the PICU cared for 60 adults with coronavirus disease 2019-related critical illness. Fifty-three required intubation and mechanical ventilation for a median of 18 days. Eighteen required renal replacement therapy and 17 died. Conclusions: During the current and potentially in future pandemics, where critical care resources are limited, pediatric intensivists and staff can be readily utilized to meaningfully contribute to the care of critically ill adults.